Health Awareness Education (HAE) Infographic: A holistic model of hygiene and cleanliness/infografik pendidikan kesedaran kesihatan dan kebersihan kendiri: Model kebersihan menyeluruh / Siti Rosnita Sakarji ... [et al.] - Sakarji, Siti Rosnita; Ahmad, Nurbarirah; Mohd Nor, Khalijah; Mohd Nor, Aishah (2021)
Cleanliness, hygiene and personal hygiene habits play an extremely important role in the development of an individual's physical and mental health, especially after the World Health Organization (WHO) declared the COVID -19 pandemic a global health problem and spread around the world. The COVID -19 virus spreads mainly through saliva droplets or discharges from the nose when an infected person coughs or sneezes. Water, sanitation and hygiene practices (WASH) had emerged as a critical component and best way to prevent and slow the transmission of the COVID -19 virus. Cleanliness and personal hygiene have not been fully understood by everyone, especially the at-risk group such as the youth. They are at greater risk of infection because their immune systems are not fully developed, and their vaccination is not yet complete. Moreover, with the explosive information nowadays, there is a need to convey the information and awareness about hygiene and cleanliness in an effective medium so that it can be well understood. The purpose of this innovation was to promote Health Awareness Education (HAE) Infographic: A Holistic Model of hygiene and cleanliness as an educational tool and to educate the society about hygiene and cleanliness in today's world. It also aims to raise awareness of the importance of hygiene and cleanliness among the public in Malaysia, especially in the education sector. Data was collected from 56 respondents from Kolej Komuniti Kuala Langat (KKKL). The result showed that students participate attentively and have a better understanding of cleanliness and hygiene education. Students agreed that they can easily understand the given information when the information is presented in form of infographic. The novelty of this product is a new educational tool that can educate the society about the importance of hygiene and cleanliness in a new norm. Moreover, HAE infographic can be recognized as a social responsibility to Malaysians.